2010
DOI: 10.1051/0004-6361/201015039
|View full text |Cite
|
Sign up to set email alerts
|

Dust grain growth inρ-Ophiuchi protoplanetary disks

Abstract: We present new ATCA observations at 3.3 mm of 27 young stellar objects in the ρ-Oph young cluster. 25 of these sources have been detected. We analyze the sub-millimeter and millimeter SED for a subsample of 17 isolated class II protoplanetary disks and derive constraints on the grain growth and total dust mass in the disk outer regions. All the disks in our sample show a mm slope of the SED which is significantly shallower than the one observed for the ISM at these long wavelengths. This indicates that 1) clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(150 citation statements)
references
References 45 publications
9
141
0
Order By: Relevance
“…7, our model images are very similar to the transition disks observations in the (sub-)millimeter regime, that reveal a continuum emission as a resolved ring-like feature (e.g., Williams & Cieza 2011;Andrews et al 2011a;Isella et al 2012). In addition, after 1 Myr of dust evolution, we estimate a spectral index of ∼2.7 by integrating the flux over the entire disk at wavelengths of 1 mm (Ricci et al 2010).…”
Section: Emission Mapssupporting
confidence: 79%
See 1 more Smart Citation
“…7, our model images are very similar to the transition disks observations in the (sub-)millimeter regime, that reveal a continuum emission as a resolved ring-like feature (e.g., Williams & Cieza 2011;Andrews et al 2011a;Isella et al 2012). In addition, after 1 Myr of dust evolution, we estimate a spectral index of ∼2.7 by integrating the flux over the entire disk at wavelengths of 1 mm (Ricci et al 2010).…”
Section: Emission Mapssupporting
confidence: 79%
“…In addition, high relative velocities lead to numerous fragmentation collisions converting a large object into smaller dust particles. The same physical process happens to the millimeter-size particles that are observed in the outer regions of the disk (e.g., Wilner et al 2000;Ricci et al 2010;Guilloteau et al 2011). One possible solution to prevent the rapid inward drift and trap dust particles is to consider pressure bumps (Klahr & Henning 1997;Fromang & Nelson 2005;Brauer et al 2008;Johansen et al 2009;Pinilla et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…It is found that, despite the young age of the cluster (∼1 Myr), many circumstellar disks in ρ Oph are evolved showing features such as millimeter size dust grains in the outer disk region (Furlan et al 2009;Andrews et al 2010;Ricci et al 2010), inner opacity holes characteristic of transition disks (Cieza et al 2010), dust settling, and dust grain processing (e.g., McClure et al 2010). In this section, and in light of the newly discovered substellar members in our survey, we use SEDs to classify the evolutionary state of each object.…”
Section: Slopes Of the Spectral Energy Distributionsmentioning
confidence: 99%
“…The grain size in protoplanetary disks has been constrained with the spectral index of the dust opacity coefficient at millimeter wavelengths (e.g., Beckwith et al 1990;Beckwith & Sargent 1991;Miyake & Nakagawa 1993;Andrews & Williams 2005;Isella et al 2009;Ricci et al 2010aRicci et al , 2010bvan der Marel et al 2013). The opacity index at millimeter wavelengths in protoplanetary disks has been shown to be as low as 0-1, which indicates that the grain size in protoplanetary disks is of the order of a millimeter or larger (e.g., Draine 2006).…”
Section: Introductionmentioning
confidence: 99%